-
The transformation of a polynomial into the product of several simplest expressions is called factoring the polynomial (also known as factoring). For example: m -n = (m+n)(m-n), so you can do this for your question.
Let m+n=a, x+y=b, then.
Original = (a-b) 2+4ab
Collation yields =(a-b) 2
If you change it back to the setting, then =(m+n-x-y) 2=(m+n-x-y)(m+n-x-y).
-
In fact, factorization is easy to open and ruin, I have already understood the factorization in the second year of junior high school in the sixth grade, the key lies in a rule: for example.
Perfect Flat, Cubic Method, Cross Multiplication, Extracting Common Factors, and more. Take cross-multiplication, for example, x 2+6x+5; x^2+22x+40;
2x 2+7x+5, where x 2+6x+5 can be analyzed like this: 6x=5x+1x=4x+2x=3x+3x, the idea is that the coefficients in front of 5x+1x are multiplied exactly 5, and the clever staring is equal to the constant term 5, so there is (x+1)(x+5); The third formula 2x 2+7x+5 can be analyzed in this way: since the coefficient of the quadratic term is not one, the sub-equation of this type has (ax + constant 1) after the confession of filial piety
bx + constant 2
a b 2, where a and b can only be 1 and 2, constant 1 constant 2 5, where constants 1 and 2 can only be 1 and 5, substituting and removing the parentheses to get (2x+5) (x+1); Once you're proficient, you'll know it at a glance.
5x^3+x^2-5x-1=(x+1)(x-1)(5x+1)
-
The minus sign means to turn b-a into a-b, which is b-a=-(-b)-=-=-(-b+a)=-(a-b).
6a(b-a)^5-2(a-b)^3=6a^5-2(a-b)^3=6a-2(a-b)^3
6a-2(a-b)^3=-6a(a-b)^5-2(a-b)^3=-2(a-b)^3*
This is the common factor].
2(a-b)^3*(3a²+3b²-6a²b+1)
-
6a(b-a)
5-2(a-b)31
Because a-b-(b-a).
So (a-b)3=
(b-a)]3
And because of (-a).
3=-a3, so (a-b)3=
b-a)3 substitutes the above formula into the original formula.
6a(b-a)
5-2(a-b)
3=6a(b-a)
5-2[-(b-a)3]
2=6a(b-a)
5+2(b-a)3=
2(b-a)
3[3a(b-a)
2+1] (omitted hereinafter).
Among the steps. 1 is the application of the opposite number, step.
2 is the application of the negative sign.
The main test points of this type of question are A-B
(b-a) and (-a).
3=-a3 application, as long as these two steps are done correctly, the remaining problems are not big. When encountering such a problem, first look at whether the inside of the parentheses is opposite to each other, if it is a single power or a double power outside the parentheses, if it is a double power, then according to.
a-b)2n=
b-a)2n, substitute it into the original formula, that is, replace b-a in parentheses with a-b.
The symbol outside the parentheses remains unchanged.
If it is a single power, it is based on.
a-b)2n+1
(b-a)2n+1 substitutes it into the original formula, replacing b-a in parentheses with a-b.
The symbol outside the parentheses is changed.
-
4m squared minus 9n squared minus 4m plus 1
4m(m-1)-(3n+1)(3n-1)2a squared plus 2b squared + 2c squared minus 2ab minus 2bc minus 2ac = (a-b) 2+(b-c) 2+(a-c) 2
-
I'll post it to you, 27 questions are a bit troublesome, and I reasoned it out in reverse.
-
Let's make two courses for you, both are similar, mention the common factor if you can, and disassemble it if you can, and there will be a result.
-
23,(19x-31)(13x-17)-(13x-17)(11x-23)
13x-17)[(19x-31)-(11x-23)]
13x 17) (8x 8), 11x 23) and (ax b) (8x c) equivalents, so a = 11, b = 23, c = 8
then, a + b + c = 11 + 23 + 8 = 42
24,a(a-1)-(a²-b)=2
a+b=2,(a-b)²=4,a²+b²-2ab=4,a²+b²)/2-ab=2。
26, a, b, c are the three sides of abc, and a +c = 2ab + 2bc 2b , a +b 2ab = 2bc b c , a b) = (b c), the above equation only holds when a = b=c, abc is equilateral.
28,2(x 1)(x 9)=2x 20+18, one item error;
2 (x 2) (x 4) = 2x 12+16, the constant term is wrong, so the original formula is 2x 12+18
Decomposition factor: 2x 12+18=2(x 3).
27. If a rational number a is equal to the square of another rational number b, then this rational number a is called a perfectly squared number.
Four consecutive natural numbers: (n 2), (n 1), n, (n + 1), then n (n + 1) (n 1) (n 2) + 1
n²-1)(n²-2n)+1
n^4-2x^3-n²+2n+1
n²-n -1) ²
So, the product of four consecutive natural numbers plus 1 is a perfectly square number.
The same conclusion would be drawn if (n 1), n, (n+1), (n+2) were used to denote four consecutive natural numbers. Details.
-
=2012²-2002×2012+2000×2002-2000×2012
2012 (2012-2002) + 2000 (2002-2012) = (2012-2002) (2012-2000) The factorization ends here.
-
1、(x-1/2)^2
2、(x+y-4z)(x+y-8z)
3. A n-1 (1 2a+3) (1 2a-3) 4.
5、-(x^n-2)(x+3)^2
6. (2x-1 2+3y)(2x-1 2-3y)7、-[1+(a+b) 2][-1+(a-b) 2]8, (a+1 8b 3n)(a-1 8b 3n) If there is a specific methodological problem, I really don't know it.
-
I didn't know how to go to high school, and I forgot all about what I didn't study in high school.
-
Remove parentheses Merge similar terms Use the formula method.
-
<> picture, Jian You, this stop and fight.
1.Knowing a=10000 and b=9999, find the value of a + b -2ab-6a + 6b + 9. >>>More
Solution: Original formula = x 2 + 4x-12
x+6) (x-2) (cross method). >>>More
The first question takes the minimum value when a=2 and b=1, the second question = 3 to the 16th power, the third question has a side length of 5, and the fourth question = -1, I am a sky walker
Useful work w=100n*2*3m=600j
The total work of the first method w1 = (100 + 400 + 20) n * 2 * 3m = 3120 J The total work of the second method w2 = (100 + 20 + 10) n * 2 * 3m = 780 J The total work of the third method w3 = (100 + 10 + 5) n * 2 * 3m = 690 J efficiency N1 = 600 3120 >>>More
1).How about or what about Original sentence meaning: Do you want to eat something? Change the meaning of the sentence: How about a bite to eat? >>>More